INDUSTRIAL PRODUCTIVITY MEASUREMENT (A Survey of the Main Methods) - Suleiman, Hassan (Dirasat in Economics and Business, 1968)
A productivity measure is the ratio between output and input both specifically and comparably defined. This ratio can be expressed in terms of a single factor input or selected inputs or all inputs combined. Thus the following broad concepts are introduced.